Biomarkers in atypical pneumonia: a systematic review of diagnostic and prognostic utility - Debashis Priyadarshan Sahoo; Bikash Ranjan Rout (Monaldi Archives for Chest Disease)
Atypical pneumonia, driven by pathogens like Mycoplasma pneumoniae, Chlamydia pneumoniae, and Legionella pneumophila, is challenging to diagnose due to non-specific symptoms. This systematic review assessed the diagnostic accuracy and prognostic value of biomarkers in atypical pneumonia. A comprehensive search of PubMed, Scopus, Web of Science, and Google Scholar (2000-2024) identified 27 studies, including observational, cohort, case-control, and review designs. Studies focused on biomarkers such as C-reactive protein (CRP), procalcitonin (PCT), ferritin, D-dimer, and pathogen-specific antibodies, with quality evaluated using the Newcastle-Ottawa Scale and AMSTAR 2. CRP was elevated in 85% of cases, with a pooled sensitivity of 82.3% [95% confidence interval (CI) 76.5-88.1, I²=78%] but moderate specificity (65.2%, 95% CI 58.0-72.4). PCT exhibited high specificity (88.7%, 95% CI 83.2-94.2, I²=65%) for bacterial etiologies, making it valuable for distinguishing bacterial from viral infections. Anti-Mycoplasma pneumoniae immunoglobulin M (IgM) showed excellent diagnostic accuracy (sensitivity 90.1%, 95% CI 85.0-95.2). Ferritin levels >400 ng/mL were strongly associated with severe outcomes [odds ratio (OR) 3.15, 95% CI 2.10-4.72, I²=70%]. Elevated biomarkers correlated with increased hospitalization (OR 2.78, 95% CI 1.95-3.96) and mortality (OR 3.42, 95% CI 2.30-5.08). Heterogeneity was significant (I²=65-78%), reflecting variability in study populations and methods. PCT and anti-Mycoplasma pneumoniae IgM enhance diagnostic precision, while ferritin and CRP are robust prognostic markers. Standardized biomarker thresholds are essential to optimize their clinical utility and improve patient outcomes in atypical pneumonia management.